Tinjauan Hukum Mengenai Perbuatan Melawan Hukum Dalam Transaksi Jual Beli Melalui Internet (E-Commerce) Dihubungakan Dengan Buku Iii Kuh Perdata - Fadjar Budianto (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
The development of the technology information has encougaded the existance of many activities performed by society through the sophisticated information technology, in this chase is internet. One of activities in the cyberg discussed in this term is electronic commerce. In the electronic commerce it self, it may create the existance of many breaking law actions. Therefore, it is essential to think the solutionof these problems in the form of law in actions, given to some tort in the electronic commerce in internet. As the consequency, such cases can be solved in law order and there will not be any vacuum of law that finally may cause a greater lost.